Organismo Uróboro de aprendizaje e interpretación nasa en torno al patrimonio del agua (2021)
Ancestral communities constitute a relevant role in the culture and socio-political development of the country, a statement evidenced in the Political Constitution of Colombia by the importance of indigenous communities within the framework of the structure of the Colombian state; However, reality exposes the opposite and in this paper the reasons why these are debated today in the universe of conflict are pointed out, a problem that leads their culture to annihilation and presents a possible solution to the various situations that They are manifested in the Andean region, specifically in the municipality of Mesetas, Meta. The work area is precisely in Meta, Colombia, where the agroecology model of indigenous communities is consolidated based on their culture and ancestral knowledge in order to protect them and avoid the risk of extinction to which they are currently exposed. for causes such as violence, armed conflict, abandonment of the state, among others.